A Woman G1P0A0 39 Weeks Pregnant with Atrial Septal Defect and Primary Infertility 6 years: Wanita G1P0A0 Hamil 39 Minggu dengan Atrial Septal Defect dan Infertilitas Primer 6 tahun - Lathifah Yasmine; Rodiani (Medula, 2022)
Congenital heart disease (CHD) or congenital heart disease is an abnormality of the structure and function of the cardiac circulation at birth. Congenital heart disease is divided into two, namely cyanotic and acyanotic. Acyanotic CHD is divided into two, namely acyanotic CHD with shunts for example ASD (Atrial Septal Defect), VSD (Ventricular Septal Defect) and PDA (Patent Ductus Arteriosus) and acyanotic CHD without shunts, examples are pulmonary stenosis. ASD (Atrial Septal Defect) is a congenital birth defect in the form of a hole in the interatrial septum that occurs due to failure of interatrial septal fusion during the fetus and is followed by pulmonary venous flow that enters the left atrium and then passes through the right atrium. Infertility is said to be primary infertility if previously a married couple failed to get pregnant after one year postpartum or post- abortion without using any contraception. Mrs. F, 33 years old, was taken to Abdu Moeloek Hospital by her family on February 6, 2022 with complaints of shortness of breath that worsened 1 day before being admitted to the hospital. A history of shortness of breath and fainting has been experienced since the patient was a teenager and was diagnosed with congenital heart disease. Vaginal toucher examination revealed anterior portio, bud opening, 25% flattening, membranes could not be assessed, cephalic presentation, Hodge II decline and pointers could not be assessed. The diagnosis in this patient was G1P0A0 39 weeks pregnant with Atrial Septal Defect and Primary Infertility 6 years. The management of this patient is observation of vital signs, administration of pharmacological therapy in the form of furosemide and sildenafil and vaginal delivery.